Identifying barriers to Irish traveller women attending breast screening. Issue 2 (May 2022) - Keane, E.; Moore, N.; Leamy, B.; Scally, A.; McEntee, M.F.
Abstract: Introduction: Breast cancer is one of the most prevalent cancers in women, however Irish Traveller women have lower breast screening rates than that of the general population. This work aims to address the gap in knowledge of Irish Traveller womens' perceptions of breast screening and the perceived barriers and enablers to attendance. Methods: This phenomenological qualitative study involves interviews with Irish Traveller women and Health Care Professionals and discusses the incentives and barriers to attending breast screening mammography in Ireland. The work investigated attitudes and decision making amongst the Irish Traveller women across breast screening and breast health. The research investigated the participants knowledge, experience and opinions about the topic of Irish Traveller womens' attendance at BreastCheck and breast health Results: Influences that create barriers to breast screening for Irish Traveller women include inequality and family/community support, fear, literacy and education, embarrassment and the health care professional, stress and appointment suitability. Findings also demonstrate inadequate data and information is available in Ireland regarding Irish Traveller women attending breast screening. Conclusion: Irish Traveller women face several influences when it comes to attending breast screening. The existing Irish national breast screening programme provides a health promotion service however, it is impossible to assess poor attendance at screening without the presence of an ethnic identifier. It would be very beneficial for screening promotion to record the ethnicity of attendees for statistical progress. This would benefit Irish Traveller women by recording the progress of attendance in the breast screening programme and creating a need for awareness and education within the annual reports. Implications for practice: Creating awareness and educating Irish Traveller women about the breast screening programme may remove barriers and lead to improved attendance rates.